THE SPEECH ACT OF SUGGESTION IN ONLINE RECIPES IN SERBIAN AND ENGLISH LANGUAGES: A RELEVANCE-THEORETIC APPROACH (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
The aim of this research was to determine the lexical and grammatical characteristics of the speech acts of suggestion in online recipes in Serbian and American English languages within the framework of relevance theory (Sperber and Wilson 1995). The suggestions were analyzed in terms of the cognitive and communicative principles and possible implicatures. The analysis was based on fifteen examples of suggestions in Serbian and fifteen examples in American English. These examples were further compared to determine whether there were certain differences as regards the speech act of suggestion. The research shows that every suggestion has its own implicatures and communicative effects depending on the form in which the suggestion is given and the succeeding co-text. As for the two languages, in this research, no significant differences arise despite a few peculiarities. There are only three instances (10%) of directly stated suggestions (e.g. my advice is, I highly recommend), one in Serbian and two in English. The other 27 examples (90%) of suggestions from both languages are given indirectly.
Keywords: recipes; culinary discourse; suggestion speech act; relevance theory; implicature